Impact of on-grid solar energy generation system on low voltage ride through capability - Mohammad Ahmad Shawqi; Mokhtar Hussien Abdallah; Ibrahim Ahmed Nassar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper represented a control strategy for photovoltaic (PV) system, this control strategy was referred to as a low voltage ride through (LVRT), it had been achieved by using three phase (3-PH) (PV) grid-connected system, where this paper discussed the way to achieve maximum output active power from the solar system, while the solar system remained connected to the grid with voltage decreasing controller techniques and this was valid until certain amount of voltage decreasing which was clarified in the results. The main goal of low voltage ride through depended on injecting reactive power to the grid, amount of the injected reactive power depended on regulations of the grid code using the control of the inverter and the strategy depended on the grid voltage drop amount. MATLAB simulation had been used to achieve what was mentioned above, which led to present various cases of achieving maximum output active power with grid voltage drops by using conventional proportional integral (PI) control of the inverter. Finally, another control method, which was proportional integral genetic algorithm (PI-GA), had been used to improve value of the generated output active power.